Effect of Long-Term Administration of Nicorandil on Endothelial Function of the Radial Artery in Patients With Angina Undergoing Transradial Percutaneous Coronary Intervention. (August 2017) - Fan, Yanming; Fu, Xianghua; Wang, Yanbo; Li, Wei; Bi, Xile; Wei, Liye; Xiao, Yuyang; Bai, Shiru
We evaluated the effect of long-term administration of nicorandil on endothelial function of the radial artery in patients with angina undergoing elective transradial coronary intervention (TRI). A total of 127 patients were randomly assigned to nicorandil (standard medication plus nicorandil 5 mg twice daily, n = 64) or control group (standard medication except nicorandil, n = 63) immediately after TRI procedure. Radial artery diameter (RAD), flow-mediated dilation (FMD), and nitroglycerin-mediated dilation (NMD) of radial artery were measured 1 day before TRI as well as 1 day and 3 months after TRI by Ultrasound-Doppler. No significant difference was observed in the baseline RAD, FMD, and NMD between the 2 groups (all P > .05). In cannulated arm, at 3-month follow-up, RAD in nicorandil group was much larger than that in the control group (2.78 ± 0.27 mm vs 2.61 ± 0.30 mm, P = .001). Besides, FMD and NMD were much higher in nicorandil group than those in the control group (10.38% ± 2.43% vs 6.81% ± 1.86%; 15.94% ± 6.28% vs 10.46% ± 5.37%, respectively, all P s < .001). In conclusion, long-term administration of nicorandil after TRI could improve the endothelial function of the cannulated radial artery.